Оценка глубины гидратообразования в нефтяных скважинах, расположенных в зоне вечной мерзлоты - Fedorov, K. M.; Vershinin, V. E.; Habibullin, R. A.; Varavva, A. I.; Федоров, К. М.; Вершинин, В. Е.; Хабибуллин, Р. А.; Варавва, А. И. (Издательство Тюменского государственного университета, 2013)
The influence of oil speed on the process of gas hydrates formation in a trunk of an oil well under intensive cooling of products due to the heat exchange with permafrost rock on the example of the Payyhskoe field has been studied. The mathematical model of oil non-isothermal transmission with dissolved gas in a vertical well has been considered. The stationary of rock temperature surrounding the well was a simplifying assumption. Analytical dependence of oil physical properties from the pressure and temperature were applied to the implementation of numerical calculation of a stream parameters. The assessment of conditions of the hydrate formation start was carried out by VNIIGAZ technique. The offered calculation procedure of thermobaric conditions in the wellbore is realized in the form of numerical algorithm. The results of numerical calculations of pressure, temperature, hydrate formation depths are given in a form of graphs. Based on the analysis of thermo-hydraulic calculations of oil flow in the wellbore the border regimes of non-hydrated oil production and the possible depths of the beginning of hydrate formation process were defined. It is shown that in a zone of wellbore passage through permafrost layers at low flow speeds there are favorable conditions for the formation of gas hydrates. Исследовано влияние скорости движения нефти на условия образования газогидратов в стволе нефтяной скважины при интенсивном охлаждении продукции за счет теплообмена с многолетнемерзлыми породами на примере Пайяхского месторождения. Рассмотрена математическая модель неизотермического движения нефти с растворенным газом в стволе вертикальной скважины. Упрощающим допущением была стационарность температуры пород, окружающих скважину. Для реализации численного расчета параметров потока были применены аналитические зависимости физических свойств нефти от давления и температуры. Оценка условий начала гидратообразования проводилась по методике ВНИИГАЗа. Предложенная в работе методика расчета термобарических условий в стволе ...